Nature, Nurture, and Institutional Norms: A Comparative Study of Left-Handed and Queer Identities. - Malmberg,Alma (2025)
This thesis investigates the parallels between experiences of left-handed individuals and queer individuals to explore how societal norms are constructed and maintained through prejudice. The study draws on theories such as social constructivism, labelling theory, symbolic interactionism, Foucault’s concept of power and knowledge, and the sociological concepts of stigma and norms. Through surveys and literary analysis, the research emphasises how both left-handedness and queerness have been historically marginalized and been subject to correction, despite being natural variations in human identity and behaviour. Data is collected through surveys that focus on personal opinions and experiences as marginalized individuals. The findings establish that social norms are not fixed truths and depend on the current collective agreements, being products of cultural narratives and institutional practices. The analysis reveals that both left-handed individuals and queer individuals encounter pressures to conform to dominant norms upheld by institutions and everyday interactions. By drawing connections between different forms of norm deviation, the thesis contributes to a broader understanding of how prejudice influences daily life.
Keywords: Left-handedness; Queerness; Stigma; Prejudice; Norms